Local structure and composition of PtRh nanoparticles produced through cathodic corrosion. Issue 16 (10th April 2017) - Hersbach, Thomas J. P.; Kortlever, Ruud; Lehtimäki, Matti; Krtil, Petr; Koper, Marc T. M.
Abstract : When preparing alloy nanoparticles through cathodic corrosion, the different corrosion behavior of the alloy components may produce both crystalline and amorphous particles. Abstract : Alloy nanoparticles fulfill an important role in catalysis. As such, producing them in a simple and clean way is much desired. A promising alloy nanoparticle production method is cathodic corrosion, which generates particles by applying an AC voltage to an alloy electrode. However, this harsh AC potential program might affect the final elemental distribution of the nanoparticles. In this work, we address this issue by characterizing the time that is required to create 1 μmol of Rh, Pt12 Rh88, Pt55 Rh45 and Pt nanoparticles under various applied potentials. The corrosion time measurements are complemented by structural characterization through transmission electron microscopy, X-ray diffraction and X-ray absorption spectroscopy. The corrosion times indicate that platinum and rhodium corrode at different rates and that the cathodic corrosion rates of the alloys are dominated by platinum. In addition, the structure-sensitive techniques reveal that the elemental distributions of the created alloy nanoparticles indeed exhibit small degrees of elemental segregation. These results indicate that the atomic alloy structure is not always preserved during cathodic corrosion.